1993
DOI: 10.1111/j.1365-3059.1993.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of disease symptoms and fungal pathogens on shoot bases in continuous winter wheat, and effects of fungicides

Abstract: Field plots in three consecutive crops of winter wheat were sampled at approximately 2‐week intervals from April to July in 1989, 1990 and 1991. Culm and stem bases were examined for symptoms of eyespot, sharp eyespot and brown foot rot. The W‐type and R‐type of Pseudocercosporella herpotrichoides, P. anguioides, Fusarium culmorum, F. avenaceum and Microdochium nivale grown from this plant material on agar were identified. Eyespot was most severe in 1991, when plant development was least rapid following cool w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 23 publications
6
29
0
Order By: Relevance
“…Nicholson et al (2002) and Ray et al (2006) found that the amount of DNA of R. cerealis, in relation to total DNA obtained from the plant, was increasing at successive development stages of wheat. Similarly in the present research, many more isolates of R. cerealis and R. solani were obtained at the end of the plant vegetation period than at the cereals seedling phase, which also coincides with the reports by Bateman (1993).…”
Section: Discussionsupporting
confidence: 79%
“…Nicholson et al (2002) and Ray et al (2006) found that the amount of DNA of R. cerealis, in relation to total DNA obtained from the plant, was increasing at successive development stages of wheat. Similarly in the present research, many more isolates of R. cerealis and R. solani were obtained at the end of the plant vegetation period than at the cereals seedling phase, which also coincides with the reports by Bateman (1993).…”
Section: Discussionsupporting
confidence: 79%
“…F. avenaceum and F. culmorum are associated with crown rot in more temperate regions overseas, such as the United Kingdom (Bateman 1993), France (Colbach et al 1996), the USA (Windels & Wiersma 1992) and Victoria, Australia (Backhouse & Burgess 2002).…”
Section: Genotypementioning
confidence: 99%
“…FRR by F. culmorum is severe when wheat is grown in warm areas, where the host plant is more subject to water stress (Bateman, ; Cariddi and Catalano, ; Chekali et al ., ; Colhoun et al ., ; Inglis and Cook, ; Papendick and Cook, ; Parry, ; Prew et al ., ). Drought conditions increase the susceptibility of the plant rather than the virulence of the fungus.…”
Section: Epidemiologymentioning
confidence: 99%